An edition of the selected letters of Samuel Rogers - May, Charlotte (2017)
This thesis offers an edition of the selected letters of the poet Samuel Rogers (1763-1855). Rogers was a member of extensive social networks in the late eighteenth and early to mid- nineteenth centuries. The Introduction looks at how the study of correspondence reveals the author to be an individual actively engaged in sociability. The content of a letter, its intended recipient, and the format of the letter itself, reveals the intricacies of the cultivation of sociability. The letter fulfils four crucial functions: to inform the recipient, thank them, ask a request of them, and create future opportunities for sociability, demonstrating the multi-faceted role of correspondence. Chapter One, ‘Rogers’s Reputation’, examines the history of Rogers’s critical reputation, which is particularly pertinent in this project which seeks to reinstate Rogers in current conversations on eighteenth and nineteenth century poets. Chapter Two, ‘Rogers and his Correspondents’, follows on from this by demonstrating how Rogers’s correspondence sheds light on professional, political and literary identities for both men and women in society.